Understanding and encouraging feedback‐seeking behaviour: a literature review. Issue 3 (8th February 2013) - Crommelinck, Michiel; Anseel, Frederik
<x xml:space="preserve">Abstract</x> Objectives The goals of this paper are to review the literature on feedback‐seeking behaviour using a self‐motives framework and to provide practical recommendations for medical educators on how to encourage feedback‐seeking behaviour. Methods To gain a better understanding of feedback‐seeking behaviour, we apply a self‐motives framework. Through this conceptual lens, we define feedback‐seeking behaviour and review its antecedents and consequences. We provide an overview of the key findings and answer to a number of unresolved issues in the literature. Results On the basis of the literature review, we present six evidence‐based insights to encourage feedback‐seeking behaviour in practice. Conclusions The literature review shows that feedback‐seeking behaviour is a valuable resource for individuals in work and educational settings as it aids their adaptation, learning and performance. Several individual and contextual factors that promote the seeking of feedback are presented. Although feedback‐seeking behaviour has been a subject of research for over 25 years, some unresolved issues remain. We present a self‐motives framework to resolve those issues and to stimulate future research. We conclude this paper with six actionable insights for medical educators based on the evidence reviewed.